2006
DOI: 10.1074/jbc.m604699200
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Heart Failure in Gαq Transgenic Mice

Abstract: For many patients with cardiac insufficiency, the disease progresses inexorably to organ dilatation, pump failure, and death. Although there are examples of reversible heart failure in man, our understanding of how the myocardium repairs itself is limited. A well defined animal model of reversible heart failure would allow us to better investigate these restorative processes. Receptors that activate G␣ q , a signal transduction molecule in the heterotrimeric G protein superfamily, are thought to play a key rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 9 publications
4
12
0
Order By: Relevance
“…2). However, consistent with our previous results (14, 22, 24), mice injected for 7 days showed a significant but moderate decrease in fractional shortening (50.4% ± 1.2 before vs. 35.7% ± 2.7 after; Fig. 2).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…2). However, consistent with our previous results (14, 22, 24), mice injected for 7 days showed a significant but moderate decrease in fractional shortening (50.4% ± 1.2 before vs. 35.7% ± 2.7 after; Fig. 2).…”
Section: Resultssupporting
confidence: 93%
“…Our Gα q Q209L mice exhibit relatively mild contractile dysfunction after 7 days of tamoxifen injections that develops into heart failure with 2–3 weeks of further treatment (14, 22). We found that autophagy was significantly increased in mice treated for 7 days, well before the onset of heart failure.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations